Determination of bioavailable iron and vitamin A in fortified blended foods and fatty acids and phytosterols in saw palmetto supplements - Penugonda, Kavitha (Kansas State University, 2016)
Fortified blended foods (FBFs), in particular, corn-soybean blend (CSB), are food aid commodities widely used in infant and young children supplementary feeding programs. A United States Agency for International Development (USAID) Food Aid Quality Review report recommended developing novel FBFs using local alternative commodities such as sorghum and improving the nutritional quality of FBFs using extrusion processing. Extruded sorghum-cowpea, sorghum-soy and corn-soy FBFs were developed and compared with the non-extruded FBFs corn-soy blend 13 (CSB13) and corn-soy blend plus (CSB+) using the in-vitro digestion/Caco-2 cell model. Dry FBFs’ iron and vitamin A content ranged from 8.0 to 31.8 mg/100g and 0.54 to 1.67 mg/100g, respectively. Following in-vitro digestion, bioavailable iron and vitamin A levels were determined by measuring Caco-2 cell ferritin and vitamin A levels in response to 12-hour and 4-hour treatments, respectively, with aqueous fractions collected from digested FBFs. Most extruded FBFs’ aqueous fraction iron levels were 2- to 7-fold higher (p<0.05) than CSB13 and CSB+. However, Caco-2 cell ferritin and vitamin A levels were not significantly different among FBFs. These results suggest that consumption of newly developed extruded sorghum-cowpea, sorghum-soy and corn-soy FBFs will result in bioavailable iron and vitamin A levels comparable to traditional non-extruded CSB13 and CSB+. Thus, extruded sorghum-cowpea FBF may be a suitable alternative to corn-soybean based FBFs. Saw palmetto supplements are one of the most commonly consumed products by men with prostate cancer and/or benign prostatic hyperplasia (BPH). Some studies have found significant improvements in BPH with saw palmetto supplementation, whereas others found no benefits. The variation in the efficacy in these trials may be a result of differences in the putative active components, fatty acids and phytosterols, of the saw palmetto supplements. We quantified fatty acids and phytosterols in 20 commercially available liquid, powder, dried berry, and tincture saw palmetto supplements. Liquid saw palmetto supplements contained significantly higher (p<0.05) concentrations of total fatty acids (908.5 mg/g), individual fatty acids, total phytosterols (2.04 mg/g), and individual phytosterols, than the other supplement categories. Our findings suggest that liquid saw palmetto supplements may be the best choice for individuals who want to take a saw palmetto supplement.
Keywords: Fortified blended foods; Bioavailability; In-vitro digestion-Caco-2 cell model; Iron and Vitamin A; Sorghum; Extrusion; Nutrition (0570)